The concept of wisdom in the Hebrew Bible: A comparative-philosophical analysis - Gericke, Jaco (Verbum et ecclesia, 2011)
This article provides a brief comparative philosophical clarification of the concept of wisdom in the Hebrew Bible. Utilising the format of a presentation presented by Ryan (2008), four philosophical definitions of wisdom were compared with similar sentiments in ancient Israelite religion: (1) wisdom as epistemic humility, (2) wisdom as factual knowledge, (3) wisdom as useful knowledge, and (4) wisdom as successful living. Cumulatively the four criteria might approximate a functional list of individually necessary and jointly sufficient conditions for instantiating the property of being wise.